Downregulation of Hypoxia-Inducible Factor-1α by RNA Interference Alleviates the Development of Collagen-Induced Arthritis in Rats - Yiping Hu; Tiantian Zhang; Jingqin Chen; WenXiang Cheng; Jianhai Chen; Zhengtan Zheng; Jietao Lin; Guoyuan Zhu; Yong Zhang; Xueling Bai; Yan Wang; Bing Song; et al. (Elsevier, 2020)
Rheumatoid arthritis (RA) is the most common type of autoimmune arthritis. Hypoxia-inducible factor-1α (HIF-1α) as a transcription factor in response to hypoxia suggests that it could be a potential therapeutic target for the treatment of RA. In this study, we assessed whether the HIF pathway blockade attenuates the manifestations of RA in the collagen-induced arthritis (CIA) rat model. We constructed a short hairpin RNA (shRNA) lentiviral expression vector targeting HIF-1α (pLVX-shRNA-HIF-1α) and to achieve HIF-1α RNA interference. Quantitative RT-PCR, immunofluorescence staining, and western blot were used to detect the expressions of HIF-1α, vascular endothelial growth factor (VEGF), phsopho (p)-p65, and p-IКBɑ mRNA and protein, respectively. Micro-computed tomography was used to investigate joint morphology at different time points after CIA induction. Moreover, enzyme-linked immunosorbent assay (ELISA) was used to monitor the expression of inflammatory cytokines. In vitro analyses revealed that pLVX-shRNA-HIF-1α effectively inhibited the expression of HIF-1α and VEGF and led to the activation of p-65 and p-IКBɑ, as well as decreased proinflammatory cytokine expression in cell culture. Inhibition of HIF-1α in rats decreased signs of a systemic inflammatory condition, together with decreased pathological changes of RA. Moreover, downregulation of HIF-1α expression markedly reduced the synovitis and angiogenesis. In conclusion, we have shown that pharmacological inhibition of HIF-1 may improve the clinical manifestations of RA. Keywords: lentivirus, rheumatoid arthritis, HIF-1α, shRNA